ORAL TRADITION AS NATURAL DISASTER MITIGATION LEARNING BASED ON LOCAL WISDOM - Nursyamsi Nursyamsi; M. Asri B.; Tamrin Tamrin; Andi Bismawati (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
The city of Palu as the capital city of Central Sulawesi Province, which developed above the Palu Koro fault, made this city prone to disasters. The events of September 28, 2018, natural disasters in the form of an earthquake, tsunami, and liquefaction devastated this city and several regencies around it. Earthquakes had often hit Central Sulawesi which had an impact on social, cultural, political and economic life, as well as the world of public education. This research purposes was to reveal the values of local wisdom of the Kaili ethnic community contained in the kayori oral tradition and traditional expressions as disaster mitigation lessons. The method used in this research was library research and analytical descriptive. Based on the results of the analysis, it showed that there were educational values, moral values, and ethical values based on local wisdom contained in the kayori oral tradition and traditional expressions. Local wisdom reflected in kayori poems and traditional expressions was the wisdom to always be ready and alert in the event of a natural disaster, no longer occupying areas that had been hit by natural disasters as residential areas, especially those on the coast because they were prone to being swept away by waves, prioritizing mutual cooperation and cooperation, prohibition to do evil and it was recommended to do good to fellow humans and other creatures.